DIFFUSION KINETICS OF FE2+ AND MG IN ALUMINOUS SPINEL - EXPERIMENTAL DETERMINATION AND APPLICATIONS - Liermann H.P.; Ganguly J. (My University, 2002)
The diffusion coefficients of Fe2+ and Mg in aluminous spinel at ~20 kb, 950 to 1325°C, and at 30 kb, 1125°C have been determined via diffusion couple experiments and numerical modeling of the induced diffusion profiles. The oxygen fugacity, fO2, was constrained by graphite encapsulating materials. The retrieved self-diffusion coefficients of Fe2+ and Mg at ~20 kb, 950 to 1325°C, fit well the Arrhenian relation, D = D0exp(-Q/RT), where Q is the activation energy, with D0(Fe) = 1.8 (+/-2.8) x 10-5, D0(Mg) = 1.9 (+/-1.4) x 10-5 cm2/s, Q(Fe) = 198 +/- 19, and Q(Mg) = 202 +/- 8 kJ/mol. Comparison with the data at 30 kb suggests an activation volume of ~5 cm3/mol. From analysis of compositional zoning in natural olivine-spinel assemblages in ultramafic rocks, previous reports concluded that D(Fe-Mg) in spinel with Cr/(Cr + Al) =<0.5 is ~10 times that in olivine. The diffusion data in spinel and olivine have been applied to the problems of preservation of Mg isotopic inhomogeneity in spinel within the plagioclase-olivine inclusions in Allende meteorite and cooling rates of terrestrial ultramafic rocks.